HOMA-AD in Assessing Insulin Resistance in Lean Noncirrhotic HCV Outpatients - Matheus Truccolo Michalczuk; Camila Rippol Kappel; Oscar Birkhan; Ana Carolina Bragança; Mário Reis Álvares-da-Silva (International Journal of Hepatology)
Introduction. There is an association between HCV and insulin resistance (IR), which is currently assessed by HOMA-IR. There is evidence that HOMA-adiponectin (HOMA-AD) is more accurate, but its role in HCV patients is unknown. The purpose of this study was to evaluate IR in an HCV sample and controls, in order to compare the accuracy of HOMA-IR and HOMA-AD. Methods. Ninety-four HCV outpatients aged <60 years who met the criteria of nondiabetic, nonobese, noncirrhotic, and nonalcohol abusers were included and compared to 29 controls. Fasting glucose, insulin, adiponectin, and lipid profiles were determined. IR was estimated by HOMA-IR and HOMA-AD. Results. The groups were similar regarding sex and BMI, but the HCV patients were older. The median insulin level was higher in the HCV group (8.6 mU/mL (6.5–13.7) versus 6.5 (4.3–10.7), P=0.004), as was median HOMA-IR (1.94 (1.51 to 3.48) versus 1.40 (1.02 to 2.36), P=0.002) and the prevalence of IR (38.3% versus 10.3% (P=0.009)). No differences were found in adiponectin levels (P=0.294) and HOMA-AD (P=0.393). Conclusion. IR is highly prevalent even in low-risk HCV outpatients. Adiponectin is not influenced by the presence of HCV. HOMA-AD does not seem to be useful in assessing IR in HCV patients.